Unified hazard models for risk assessment of transportation networks in a multi-hazard environment. (1st June 2022) - Karatzetzou, Anna; Stefanidis, Stefanos; Stefanidou, Sotiria; Tsinidis, Grigorios; Pitilakis, Dimitris
Abstract: Transportation networks play a vital role in the economic prosperity of modern societies. Recent hazardous events in Greece, for instance, the 2021 Crete earthquake, the 2021 Thessaly earthquakes and floods, and the heavy 2019 rainfall in Crete, have revealed the vulnerability of roadway networks to natural hazards, resulting in severe physical damage and important economic and societal losses. Severe damage on bridges and tunnels of roadway networks is commonly related to the effects of multiple hazards that may act independently during their life span. However, the literature on risk assessment of the above elements commonly focuses on the effects of a single hazard, disregarding the effects of various hazards in a multi-hazard environment. In this context, there is an increasing need for a reasonable and practical evaluation of the multi-hazard risk of transportation infrastructure. Research project INFRARES (https://www.infrares.gr/ ) aspires to gain further insight into the risk and resilience assessment of bridges and tunnels subjected to independent and/or multiple subsequent natural hazards, proposing a comprehensive framework toward a more efficient risk assessment of the above critical transportation infrastructure components. This paper presents the first part of the framework. More specifically, a unified methodology for the development and graphic presentation of single seismic- and flood-hazard scenarios, as well as of novel multi-seismic-flood hazard scenarios, are presented, providing a valuable tool for risk assessment of roadway networks for separate, combined (triggered), or subsequent hazards. The unified approach followed to develop single seismic and flood hazard scenarios is initially presented. The data required to develop such scenarios are derived from recently published and freely available data accessible via European databases; hence, allowing for a straightforward application of the proposed methodology throughout Europe. The unified approach in developing single hazard scenarios is further exploited to develop integrated seismic-flood hazard scenarios. Single and multi-hazard scenarios are graphically displayed in the form of GIS format maps, with the methodology being applied to the Greek terrain for various hazard scenarios. Recent hazard events that caused significant damage to the Greek road network are also presented to emphasize the importance of proper evaluation of natural hazards and their effects on roadway networks in multi-hazard environments. The methodology developed within this study contributes toward the generation of uniform multi-hazard scenarios for the risk assessment of various structures and networks in a multi-hazard environment.